IJCM_134A: Community Engagement Strategies for Prevention and Control of Non-communicable Diseases in Primary Healthcare Settings: A review of evidences from Low- and Middle-income countries - Banerjee Sitikantha; Kumar Dinesh; Kumar Nitesh; Choudhary Neha; Bandyopadhyay Kajari (Wolters Kluwer Medknow Publications, 2024)
Background: Community engagement is considered as one of the pillars in successful implementation program for prevention and control of Non- Communicable Diseases (NCDs). Objective: To gather evidence from the available literature concerning effective strategies for enhancing community engagement in primary healthcare for NCD prevention, which are appropriate for resource constraint settings in low- and middle-income countries. Methodology: This study followed the Preferred Reporting Items for Systematic reviews and Meta-Analysis for Scoping Reviews (PRISMA- ScR) guidelines. Original articles and reports published from January 2000 to September 2023, in English language; with the following designs- Randomized controlled trials with single or multiple arms, quasi- experimental studies, public health practices and qualitative studies, available online were included in this review. Digital databases like PubMed and Google scholar were searched to find out articles, using a pre-designed peer- reviewed search strategy by combining established search terms and free text terms. Further, hand search was made by going through the references of the retrieved articles. All publications were independently evaluated by two reviewers. Information extracted from the published articles were recorded using a pre-designed data extraction sheet in Microsoft excel. Results: Key interventions emerged from the review included group-based peer support program; family level intervention; setting based approach (Health Promoting school /institution /market /hospital); advocacy, network and counselling among People Living with NCDs etc. Evidence also suggested use of appropriate technology such as CPHC-NCD Software, generation of Ayushman Bharat-Health Account IDs (ABHA IDs) through National NCD Portal, maintenance of NCD data record and register in digital formats on National NCD Portal and spreading community dialog using mass media, digital media and social media. Conclusion: The findings of this study will guide the development and implementation of evidence-based interventions for prevention of NCDs using primary healthcare platform suitable for resource limited settings.